The Effects of Angularity Number on Texture Depths and Skid Resistance of Stone Mastic Asphalt - Musa, Mohtady Ali (2002)
Skidding of vehicles due to the lack of friction between pavement and tires, especially on wet pavements, is a problem to road users. There are many parameters that can help in attaining higher friction of pavement to control skidding such as microtexture and macrotexture of stones. One of the controlling parameters for macrotexture is the shape of stones for pavement construction. This research examines the angularity and related characteristics of aggregates for the formulation of high friction stone mastic asphalt wearing course. In this study, only a small range of aggregate angularities could be produced using a UPM crushing machine. Hence, attempts to produce a wider range of angularities were aborted. Out of eighty one quarries investigated, only eight quarries were found suitable for this study. This is because of their different crushing systems which produce a wide range of angularities. The collected aggregate materials were analysed for their Angularity Number and the Particle Shape Index as well as the other physical properties including petrography study. These aggregate materials were then mixed with the optimum content of 60- 70 penetration grade asphalt cement as determined by the UPM in-house method of mix design. A total of one hundred and twenty samples were then casted. These samples were examined for their density, resilient modulus, and voids. The performance tests namely, Marshal stability, flow, static and dynamic creep modulus, and indirect tensile strength test were carried out. Regression analysis was done to correlate the aggregate Angularity Number with the stability, resilient modulus, density, Voids in Total Mix (VTM), Voids in Mineral Aggregate (VMA), static recovery efficiency and Surface Area (SA) using Microsoft EX CEL. The correlation was determined according to the value of the coefficient of regression. The result of the regression showed that there is a significant correlation of the density, VTM, VMA and SA with the Angularity Number. Slab samples of size 0.43m x 0.43m x 0.043m were prepared from the different crushed quarry aggregates. The British Pendulum Number (BPN) and the Texture Depth (TO) were determined using the British portable skid tester and the sand patch methods, respectively. The regression analysis was performed to correlate the BPN with AN, SA, VMA anu TD and to correlate VTM, TD and density with AN. The results of the regression showed that there is a correlation of skid resistance with AN, VMA, and also there is a correlation between TD and AN (R2= 0.67).